Thromboaspiration in the Basilar Artery: Report of Two Cases - Chapot, René; Houdart, Emmanuel; Rogopoulos, André; Mounayer, Charbel; Saint-Maurice, Jean-Pierre; Merland, Jean-Jacques (American Journal of Neuroradiology, 2002)
Summary: Recanalization of the basilar artery is not always achieved with intraarterial fibrinolysis. We report two cases of thromboaspiration in the basilar artery in which recanalization with fibrinolysis was successful. Thromboaspiration requires favorable anatomy and a fresh nonadhesive clot. It reduces the time for recanalization, has no hemorrhagic risk, and may prevent distal clot migration. Thromboaspiration may be attempted as an adjunct or alternative to intraarterial fibrinolysis for basilar artery recanalization.